THE ROLE OF KAIZEN MEDIATION IN THE RELATIONSHIP BETWEEN TOTAL QUALITY MANAGEMENT AND SERVICE QUALITY FOR EMPLOYEES AT PRATAMA MANDHERE HOSPITAL, WEST NIAS REGENCY - Forman Halawa; Eliyunus Waruwu; Marinus Gea (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2024)
This study aims to investigate the influence of Total Quality Management (TQM) on service quality, mediated by Kaizen, at Pratama Mandrehe Hospital in Nias Barat Regency. The research method employed is quantitative, distributing questionnaires to 60 employees of Pratama Mandrehe Hospital in Nias Barat. The analysis method used is SEM PLS with a bootstrapping technique to test the proposed hypotheses. The results indicate that Kaizen has a positive and significant effect on service quality (coefficient = 0.399, p < 0.05), and TQM has a positive and significant effect on Kaizen (coefficient = 0.603, p < 0.05). Furthermore, the findings also demonstrate that TQM influences service quality mediated by Kaizen (coefficient = 0.241, p < 0.05). The practical implications of this study underscore the importance of implementing Kaizen strategies to enhance service quality in hospitals, as well as the need for integrating TQM and Kaizen in overall quality management. This research contributes to the development of quality management practices in the healthcare sector, particularly in the context of hospitals in developing areas.